Produção científica brasileira em oncologia na base de dados Web of Science, utilizando o Índice H (Índice de Hirsch): 2013-2015 - ARAUJO, Andreza Silva (2017)
Analyze the scientific production in Oncology from the period 2013 to 2015 by using the H index, and as a reference database, the Web of Science (WoS). The term adopted for the research "medical oncology," was chosen by consulting the Medical Subject Headings, MeSH, and then refinements were made to get the number of actual study results. Were recovered 52 results in total, and were recovered 100 authors (by record count), but only were used in the research those who had two or more citations. After this further refinement recovered 20 authors, which were analyzed their respective H index. It was concluded that despite being an important tool designed to facilitate the measurement of scientific productivity, the H index couldn’t measure the actual participation of each author analyzed. The results are important, but all the disadvantages presented by him, hinder a more concrete analysis that can be achieved by analyzing the impact factor of a journal, for example.